2013
DOI: 10.1136/gutjnl-2012-304292
|View full text |Cite
|
Sign up to set email alerts
|

Telephone-based re-education on the day before colonoscopy improves the quality of bowel preparation and the polyp detection rate: a prospective, colonoscopist-blinded, randomised, controlled study

Abstract: TRE about the details of bowel preparation on the day before colonoscopy significantly improved the quality of bowel preparation and PDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
178
4
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(206 citation statements)
references
References 30 publications
7
178
4
7
Order By: Relevance
“…This was true in both study groups. Further, despite recent evidence reporting high rates (10%-30%) of inadequate preparation, particularly when performed at home (7,10,12,15,23) , our study found that almost all patients had adequate preparation, regardless of having had home or hospital preparation. The fact that our study population was composed only by ASA I and II patients could explain such a good preparation quality.…”
Section: Discussioncontrasting
confidence: 99%
“…This was true in both study groups. Further, despite recent evidence reporting high rates (10%-30%) of inadequate preparation, particularly when performed at home (7,10,12,15,23) , our study found that almost all patients had adequate preparation, regardless of having had home or hospital preparation. The fact that our study population was composed only by ASA I and II patients could explain such a good preparation quality.…”
Section: Discussioncontrasting
confidence: 99%
“…The SCOPE SC program chose to deploy FQHCs as the patient recruiting sites and provided funds to cover colonoscopy costs and patient navigation, which yielded highly encouraging results: rapid accrual of targeted beneficiaries, very high procedure completion rate of 85.0%, and high rates of acceptable bowel preparation. The critical role of patient navigation in improving bowel preparation and adenoma detection is well documented [2426]. The procedure completion rate of 85% exceeds the documented rate of 66% following structured patient navigation efforts in New York City [9] and is similar to a recently documented rate of 91% colonoscopy completion following a comprehensive patient navigator program in New York City [27].…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, if waiting times to colonoscopy can not be reduced, more contact such as via telephone, e-mail, and short message service (SMS) may be useful to remind patients about the bowel preparation process. Liu et al (18) reported that telephone-based re-education the day before colonoscopy improved the quality of bowel preparation and the polyp detection rate. Several previous studies found that telephone and SMS reminders were associated with an improvement in outpatient attendance (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%